Estimating the carbon footprint of Ethiopian higher education institutions: A case study of Debre Markos University - Marshet M. Admas; Lena D. Mensah; Denis E.K. Dzebre; Richard Arthur; David A. Quansah (Results in Engineering)
The increasing concern for environmental sustainability has prompted various sectors to evaluate their impact on climate change. Higher education institutions (HEIs) significantly contribute to environmental awareness and sustainability in addition to knowledge advancement. This study is aimed to identify emission sources and estimate the carbon footprint of Debre Markos University (DMU), Ethiopia using the greenhouse gas (GHG) protocol standard developed by the World Resources Institute (WRI) and the World Business Council for Sustainable Development (WBCSD). A total of 6420 tCO2eq was estimated for the university. Scope 1 emissions contributed 64 % of the total, while Scope 2 and Scope 3 contributed 5 % and 31 % respectively. Quantifying carbon footprint of HEIs is important in comprehending their environmental impact and promoting sustainable practices. This study presents the first carbon footprint assessment of Ethiopian higher education institutions, providing insights to guide policy development, enhance sustainability, and support Ethiopia's Nationally Determined Contribution (NDC) targets.